Penilaian Kualitas Air Sungai Lumay sebagai Air Baku Perusahaan Daerah Air Minum di Kabupaten Ogan Komering Ulu Selatan - Sri Rahayu Ayu; Dade Jubaedah; Imroatul Chalimah Juliana (Dampak, 2026)
The Lumay River is a river that flows into the Komering Sub-watershed and provides raw water to the regional water utility. The purpose of this study is to evaluate whether the Lumay River's water is suitable for use as raw water by the regional water business, as well as to examine the Lumay River's water quality using physical, chemical, and biological characteristics. In September 2025, temperature, pH, TDS, TSS, BOD, COD, Nitrate, Ammonia, Total Phosphate, and Total Coliform were measured using the grab sample method and assessed using the Pollution Index (PI). The study's findings indicate that the Lumay River's water quality is classified as slightly contaminated at all monitoring stations, with pollution index values of 1.8, 2.7, and 1.8 when compared to Class I river water quality requirements. Meanwhile, monitoring point one has good pollution index values when compared to Class II river water quality criteria, however monitoring points two and three have slightly contaminated values of 0.7, 1.6, and 1.7, respectively. Four values exceed Class I quality norms: DO, COD, Ammonia, Total Phosphate, and Total Coliform, with Total Phosphate being the only parameter that exceeds Class II quality standards. The Lumay River can still be used for its primary purpose, particularly as raw water for PDAM (Regional Water Company), although it requires additional treatment before being delivered to the public.